Parhyale explorator, a new species of talitroid amphipod from the bay of Arcachon, France - Arresti (Bull. Mus. natn. Hist. nat., Paris, 4" ser., 11, 1989, section A, n° 1 : 101-115., 1989)
Parhyale explorator n. sp., is a new species of talitroid amphipod discovered in the Bay of Arcachon (France). P. explorator's most distinguishing features are the long tufts of plumose setae ventrally on antenna 2 which make it easy to differentiate from other species of the genus. This article presents a detailed description of the new species together with a discussion of amphipod systematics and the key, proposed by BARNARD (1979), that is developed using all species found to date.